The genus Cixius Latreille, 1804 (Hemiptera, Fulgoromorpha, Cixiidae) in Lebanon with the description of two new species - Picciau, Luca; Hoch, Hannelore; Tedeschi, Rosemarie; Alma, Alberto (Zootaxa, 2016)
A first list of Cixius fauna of Lebanon is here provided with the description of two new species: one within the subgenus Acanthocixius, Cixius bifidispinus sp. nov. and one within the subgenus Ceratocixius Cixius superremotus sp. nov. The standard morphological description is supplemented by sequence data of the mitochondrial cytochrome c oxidase subunit I (COI) gene fragment. Some notes on their distribution and economic importance are also reported.